A Manifesto for the Just City: Volume 4 (TU Delft OPEN Books, 2025)
The workshop Manifesto for the Just City is a digital lecture and debate series composed of four online sessions with leading academics and practitioners in the fields of urban theory, urban planning and spatial justice. Upon participation in the online lecture series, teams of students are invited to draft a Manifesto for the Just City, expressing their visions for cities that are sustainable, fair and inclusive for all. This activity is organised by the TU Delft Centre for the Just City, and partners. This activity is supported by the Delft Design for Values Institute (DDfV), the TU Delft platform for discussing values in technology and design. The Manifesto for the Just City is a publication by the TU Delft Centre for the Just City